The rights of the indigenous peoples to self determination: attempts to address the violation of human rights with specific reference to Mali - Tung, Odile Lim (University of Pretoria, 2011)
Thesis (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2010.